Multilevel certification system for engineers - Kiriukhin, M.M (Наука, технології, інновації, 2017)
Multilevel certification system was proposed, which is based on existing procedures in the world and in Europe. The system covers all the period of possessor’s carrier: from the school till own engineering projects and honorable titles. New levels are included to the system, e.g. for school and university students. Engineering certificates and personal data of applicants should be saved in e-register. This register is built similar to so called labor book for Soviet Union employees.